Generalized geometric triangulation algorithm for mobile robot absolute self-localization - Esteves, João Sena (2003)
Triangulation with active beacons is widely used in the absolute localization of mobile robots. The Geometric Triangulation algorithm allows the self- localization of a robot on a plane. However, the three beacons it uses must be “properly ordered” and the algorithm works consistently only when the robot is within the triangle formed by these beacons. This paper presents an improved version of the algorithm, which does not require beacon ordering and works over the whole navigation plane except for a few well-determined lines where localization is not possible.